The cue-of-the-cloud effect: when reminders of online information availability increase purchase intentions and choice - Bhargave,RP; Mantonakis,A; White,K (Journal of Marketing Research, 2016)
In offline purchasing settings (e.g., retail stores), consumers often encounter reminders that product information can be found on the Internet. The authors refer to a reminder of the availability of online information as a ‘cue-of-the-cloud’ and explore its unique consequences on offline consumer behavior. This research finds that when consumers are presented with relatively large amounts of information in offline purchasing situations, a cue-of-the-cloud can enhance purchase intentions and choice behaviors. This occurs because the cue increases consumers' confidence in being able to retain and access the information seen in-store, which engenders positive feelings about the decision to purchase. Four studies, including two experiments in real brick-and-mortar field settings, demonstrate the consequence of a cue-of-the-cloud, along with some novel moderators of these effects.